2008
DOI: 10.1021/es702745d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Responses to Chronic Cadmium, Fluoranthene, and Atrazine Exposure in Lumbricus rubellus

Abstract: Transcriptional responses of a soil-dwelling organism (the earthworm Lumbricus rubellus) to three chemicals, cadmium (Cd), fluoranthene (FA), and atrazine (AZ), were measured following chronic exposure, with the aim of identifying the nature of any shared transcriptional response. Principal component analysis indicated full or partial separation of control and exposed samples for each compound but not for the composite set of all control and exposed samples. Partial least-squares discriminant analysis allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…E. fetida and L. rubellus are the only two species to date to have cDNA microarrays available for more comprehensive ecotoxicogenomic studies (Gong et al 2007;Owen et al 2008;Svendsen et al 2008), and have obvious advantages for laboratory and field studies respectively, given their status as an important ecotoxicological model (E. fetida), and the extent of already existing metabolomic data and greater relevance to soil contamination (L. rubellus). Studies have been carried out at various levels of environmental relevance (paper contact test, spiked soil exposures, and actual contaminated sites), and for both toxic metals (copper, cadmium, and metal contaminated sites) and organics (pesticides, and model aromatic compounds).…”
Section: Laboratory Studies Of Terrestrial Organismsmentioning
confidence: 99%
“…E. fetida and L. rubellus are the only two species to date to have cDNA microarrays available for more comprehensive ecotoxicogenomic studies (Gong et al 2007;Owen et al 2008;Svendsen et al 2008), and have obvious advantages for laboratory and field studies respectively, given their status as an important ecotoxicological model (E. fetida), and the extent of already existing metabolomic data and greater relevance to soil contamination (L. rubellus). Studies have been carried out at various levels of environmental relevance (paper contact test, spiked soil exposures, and actual contaminated sites), and for both toxic metals (copper, cadmium, and metal contaminated sites) and organics (pesticides, and model aromatic compounds).…”
Section: Laboratory Studies Of Terrestrial Organismsmentioning
confidence: 99%
“…Similarly, Nota and co-workers recently identified a set of 188 genes from expression profiles of the springtail ( Folsomia candida ) exposed to a soil spiked with six different metals using the uncorrelated shrunken centroid method, and predicted an independent test soils set with an accuracy of 83% but failed on field soils collected from two cobalt-contaminated sites using this gene set [11]. Several other studies also reported a varying degree of success in the identification of classifier genes in both aquatic species like the zebrafish ( Danio rerio ) [12], the common carp Cyprinus carpio [14] and the water flea Daphnia magna [15], and terrestrial organisms such as the earthworm Lumbricus rubellus [16].…”
Section: Introductionmentioning
confidence: 97%
“…The measurement of toxicant induced impacts on gene and protein expression and metabolite concentrations offer the chance to understand how effects on life history are mediated at the molecular level. The use of toxicogenomics in ecotoxicology is rapidly evolving and increasing (Williams et al 2003; Heckmann et al 2006; Soetaert et al 2007; Svendsen et al 2008; Owen et al 2008; Bundy et al 2008). To date, however, only a few of these studies have attempted to link gene/protein expression responses to life history changes elicited by toxicant exposure (Connon et al 2008; Swain et al 2010).…”
Section: Introductionmentioning
confidence: 99%